J Obstet Gynecol Cancer Res 2019
DOI: 10.30699/jogcr.4.4.135
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between correction of Menstrual Irregularity and Diminution of Cyclic Mastalgia

Abstract: Background & Objective: Cyclic mastalgia is clinically related to alterations in sex hormone levels during the menstrual cycle. A derangement in normal menstrual cycle leads to exacerbated mastalgia; which can also cause menstrual irregularities and abnormal uterine bleeding (AUB). A decrease in severity of mastalgia is observed in patients with simultaneous cyclic mastalgia and menstrual irregularities/AUB, following correction of menstrual irregularity. This study was designed and conducted to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The preponderance of negative/normal findings on imaging in the present study agrees with some previous studies, especially those in the setting of a normal CBE (9,17,20). In this study, 76% of the patients revealed no abnormality on imaging, which is similar to two reports in the USA (77.3% and 75%) (16,17).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The preponderance of negative/normal findings on imaging in the present study agrees with some previous studies, especially those in the setting of a normal CBE (9,17,20). In this study, 76% of the patients revealed no abnormality on imaging, which is similar to two reports in the USA (77.3% and 75%) (16,17).…”
Section: Discussionsupporting
confidence: 92%
“…Other factors associated with breast pain are caffeine and nicotine consumption, lactation frequency, alteration in estrogen/progesterone ratio, oral contraceptives, hormonal therapy, psychotropic drugs, and others (10,14,16,28). Large breasts also cause some degree of ligamentous pain (9). In the aforementioned cases, negative/normal imaging findings are usually observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations